1988
DOI: 10.1002/jobm.3620280106
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise increase of elongation rate in individual hyphae of Streptomyces granaticolor during outgrowth

Abstract: Starting with germinating spores of Streptornyces granaticolor, the kinetics of elongation of 3 types of outgrowing hyphae was determined. The 3 hyphal types were: first germ tube, second germ tube (which appeared from the same spores about 3 hours later) and branches arising from the first germ tubes. Taking photographs every fifth minute, with all hyphae a linear multiphasic elongation behaviour was found. Alternatively, periods with constant elongation rate (a) changed with steps at which a increased abrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
(9 reference statements)
1
8
0
Order By: Relevance
“…Thus, it has been reported that germ tubes of S. hygroscopicus elongated exponentially [3], whereas in S. coelicolor they elongated linearly [5]. Exponential kinetics of elongation were initially also reported for S. granaticolor [4], but further studies using a more detailed mode of observation revealed that in this microorganism the germ tubes elongate linearly [11]. All these observations have been made on cultures of streptomycetes grown on solid media.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, it has been reported that germ tubes of S. hygroscopicus elongated exponentially [3], whereas in S. coelicolor they elongated linearly [5]. Exponential kinetics of elongation were initially also reported for S. granaticolor [4], but further studies using a more detailed mode of observation revealed that in this microorganism the germ tubes elongate linearly [11]. All these observations have been made on cultures of streptomycetes grown on solid media.…”
Section: Discussionmentioning
confidence: 96%
“…Using these cultures it was possible to investigate the pattern of growth during the initial steps of hy-phal development. This topic has been the subject of contradictory reports [11]. Thus, it has been reported that germ tubes of S. hygroscopicus elongated exponentially [3], whereas in S. coelicolor they elongated linearly [5].…”
Section: Discussionmentioning
confidence: 99%
“…Looking for a factor which may be responsible for the timing of septation, a coordination by means of DNA replication events seems, at first sight, to be missing. Namely, even at very slow rates of growth (doubling times of several hours) the new-born daughter cells contain 6 (in c2) and 8 (in c l ) nucleoids, since the unit cell length in vitro accounts for 1.1 pm (KRETSCHMER and KUMMER 1987). But, when for the fast growing cultures the time T between two successive septations is calculated (Table 2), the values are quite identical to the replication time C, which was 46 min in glucose-peptone medium (KRETSCHMER 1988), and 52 min in glucose-casamino acids medium (z = 96 min, KUMMER and KRETSCHMER 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Namely, even at very slow rates of growth (doubling times of several hours) the new-born daughter cells contain 6 (in c2) and 8 (in c l ) nucleoids, since the unit cell length in vitro accounts for 1.1 pm (KRETSCHMER and KUMMER 1987). But, when for the fast growing cultures the time T between two successive septations is calculated (Table 2), the values are quite identical to the replication time C, which was 46 min in glucose-peptone medium (KRETSCHMER 1988), and 52 min in glucose-casamino acids medium (z = 96 min, KUMMER and KRETSCHMER 1986). This similarity between Tand Cat fast rates of growth leads us to the conclusion that the timing of septation is determined with the rhythm of DNA replication, if the apical cell has attained a certain length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation